Labor Market Frictions and Spillover Effects from Publicly Announced Sectoral Minimum Wages - Gökay Demir (Institute of Labor Economics (IZA), 2024)
This paper analyzes the horizontal spillover effects of Germany's first sectoral minimum wage. Using a difference-in-differences estimation, I examine the impact of the public announcement and introduction of the minimum wage on sub-minimum wage workers in related jobs outside the minimum wage sector, defined using employment flows. I find an increase in wages and job-to-job transitions for sub-minimum wage workers in related jobs. The spillover effects are driven by workers who reallocate to better-paying establishments, have low labor market experience, and are more closely connected to the minimum wage sector by having former coworkers in that sector.
Keywords: J31; J38; J42; J62; 330; spillover; outside option; labor market frictions; minimum wages